Association of Life-Course Educational Attainment and Breast Cancer Grade in the MEND Study. Issue 1 (7th July 2021) - Gupta, Anjali; Jones, Kelley; Deveaux, April; Bevel, Malcolm; Salako, Omolola; Daramola, Adetola; Hall, Allison; Alatise, Olusegun; Ogun, Gabriel; Adeniyi, Adewale; Ojo, Akinlolu; Ayandipo, Omobolaji; et al.
Background: Nigeria reports the highest age-standardized mortality rate for breast cancer (BC) among African countries and disproportionately high rates of high-grade cancer. Histological grade is a strong predictor of mortality, and evidence suggests that educational attainment influences cancer outcomes. Objective: We characterize the association between educational trends across the life-course and BC grade at diagnosis. Methods: Data on 224 BC patients enrolled in the Mechanisms for Established and Novel Risk Factors for Breast Cancer in Nigerian Women (MEND) study was analyzed. Participant and parental (mother and father) education was categorized as low (primary school or less) or high (secondary school or greater). Accordingly, the educational trend across the life-course was determined for each participant relative to each parent: stable high, increasing, decreasing, or stable low. BC grade was classified as high (grade 3) or low (grades 1–2). Findings: About 34% of participants, 71% of fathers, and 85% of mothers had low education. Approximately one-third of participants were diagnosed with high-grade BC. Participants with low-grade BC were more likely to have highly educated fathers (p = 0.04). After adjusting for age, comorbidities, marital status and mammogram screening, participants with highly educated fathers were 60% less likely to have high-grade BC (aOR 0.41; 95% CI 0.20 to 0.84) compared to those with less-educated fathers. Stable high life-course education relative to father was also associated with a significantly lower likelihood of having high-grade BC (aOR 0.36; 95% CI 0.15 to 0.87) compared to stable low life-course education. No significant associations were observed for the participant's education, mother's education, or life-course education relative to mother. Conclusions: Early-life socioeconomic status (SES) may influence BC grade. This deserves further study to inform policies that may be useful in reducing high-grade BC in Nigeria.